Spatial Analysis of Visual Pollution in the City of Amara - Ali Haman Al-Bahadli , Assist .Lect. Tahseen; Jabbar Latif Al-Maamouri , Assist .Lect. Husam (Basra studies journal, 2024)
Most cities nowadays are experiencing rapid development, especially in developing countries. There is an urgent need to care for the environment due to the serious deterioration witnessed in urban centers, which have become unsafe, unclean, and filled with litter. They are visually distorted with walls covered in writings, images, and advertisements, in addition to crowded streets filled with vehicles and the juxtaposition of old and modern buildings. This necessitates attention to planning and urban aspects, focusing on aesthetic and visual elements in the heart of cities. The aim of the research was to study visual pollution in the city of Amara, identify its main aspects, causes, factors leading to its emergence, and its extent of spread in the study area. The research addressed the most significant problems resulting from the spread of pollution in the city's neighborhoods, indicating that it poses a serious indirect threat to the lives of residents. The danger of pollution lies in its connection that diminishes the sense of beauty, collapses aesthetic considerations, and acceptance of the ugly image, spreading it without being noticed by the population.